Role of Living Anatomy in Medical Education: A Narrative Review - Mohammad R Asad; Ahmed Al Mutairi; Raed E AlZahrani; Mohammad M Ahmed; Mohammed Nazeer; Mohamed Taha (Wolters Kluwer Medknow Publications, 2023)
Introduction: There has been a significant change noticed in the way in how anatomy is taught and learned in last two decades. The use of teaching approaches such as body painting, peer physical examination, medical imaging, and virtual anatomy software in the teaching and learning of living anatomy was made possible by advancements in medical technology. This study focuses on a review of the historical context and contemporary developments in teaching and learning of live and surface anatomy with a special emphasis on its pedagogical elements, some opinions of medical educationists, and undergraduates. Conclusions: It is suggested that living anatomy be included as a core subject in the curriculum. Learning about living anatomy will be improved in an integrated and pertinent framework with the inclusion and execution of teaching and learning modalities such as body painting, peer physical examination, medical imaging, and virtual anatomy software.